Proofreading workshop in collaboration with ITBM 2019 / Mohd Hafiz Mat Adam - Mat Adam, Mohd Hafiz (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
The Academy of Language Studies (APB), UiTM Perak Branch, Tapah Campus had organised the Proofread-ing Workshop on the January 7 - 9, 2019. The workshop was a collaboration between UiTM Perak Branch Tap-ah Campus and Malaysia Institute of Translation and Books (ITBM). The workshop was organised to expand the knowledge of proofreading amongst language lec-turers in UiTM Perak Branch and participants from other institutions namely PICOMS and AGRO Bank. The partic-ipants were awarded with certificates which validated them as certified proofreaders. This workshop trained the participants to check and correct syntax errors in theses, articles, journals and many other categories of writings.